The Role of Organizational Commitment Mediation on The Influence of Organizational Culture on The Performance of Private University Education Personnel In Banten Province - Kurniasih, Dedeh; Triatmanto, Boge; Supriadi, Bambang (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study aims to examine the influence of organizational culture on the performance of education personnel through organizational commitment, both directly and indirectly. The research was conducted using a quantitative method. Data collection using questionnaires for education personnel working at private universities accredited "Very Good" or "B" in the Banten Province area was obtained by 152 respondents who were selected using proportional random sampling. The data was analyzed using the SEM (structure equation modelling) method operated through the AMOS program. The results of the study show that organizational culture, organizational commitment, and performance of education personnel are important concepts in human resource management that are interrelated. A strong organizational culture can increase organizational commitment, which in turn can drive improved employee performance. organizational culture has a positive and significant influence on the performance of education personnel, organizational culture has a significant influence on organizational commitment, organizational commitment has a positive and significant influence on the performance of education personnel, organizational commitment is able to mediate the influence of organizational culture on the performance of private university education personnel in Banten Province.